(untitled) (Revista de Crítica Literaria Latinoamericana, 2016)
In the Apologético en favor de don Luis de Góngora, Espinosa Medrano defines poetry as a style “without heart from any mystery.” After a brief review of the concept of mystery in the exegetical tradition, exemplified with a sermon by El Lunarejo, I explore in the text of Apologético the consequences of such a negative definition of poetry through a commented reading of both Faria and Espinosa Medrano. Then I delve into the poetry of El Lunarejo, analyzing his theoretical definitions of style and his comments on two verses of Gongora’s Polifemo: a hyperbaton and a metaphor. My findings help to clarify the apparent antihumanism of Espinosa Medrano, one of the last exponents in the debate around Gongora and one of Gongora’s first supporters in the Americas.